Heidegger's contributions to philosophy : an introduction - Vallega-Neu, Daniela, 1966- (Studies in Continental thought., 2003)
In her consise introduction to Contributions to Philosophy, Vallega-Neu provides guidance and structure to readers attempting to navigate this much-discussed but difficult text. In view of the centrality of Being and Time to Heidegger interpretation in recent decades, the author introduces Contributions first by reconsidering Being and Time in light of the transformative turn from prepositional thought to the poietic, performative character of thinking and language that markes the passage between the two works.